Schwann-cell-derived CMTM6 restricts radial axonal growth - Elazar, Nimrod (Nat Commun, 2020)
Myelinating Schwann cells control the diameter of the axons they ensheath by an unknown mechanism. In a recent article in Nature Communications, Eichel and colleagues identify the tetraspan protein CMTM6 as a regulator of axonal caliber.